SMART GLOVE USAGE POSSIBILITY FOR BASKETBALL TRAINING: PROOF OF CONCEPT - Oks J., Aleksander; Oks, Alexander; Katashev, Alexei; Eizentals, Peteris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Nowadays, basketball is one of the most entertaining and popular sports. In the last years, the number of people that are dedicating themselves to basketball has grown rapidly. The increasing number of sportsmen defines the increasing demand to monitor and analyse their performance, hereby granting the possibility to review and evaluate mistakes made within different game phases, which, in turn, would be useful for future training. The present research is the first step to develop a wireless system (Smart Basketball Glove (SBG)) for basketball shot analysis and training. SBG system is based on knitted tension and pressure sensors that were already successfully used in Smart Socks and Smart Shirt applications. These sensors, while embedded into the proposed system’s textile part, showed high tactile sensitivity and speed of response and, therefore, demonstrates potential abilities to analyse the wrist and fingers movement and estimate the forces with which fingers interact with the ball during basketball shot. Necessary requirements for data acquisition and transition device of SBG are formulated for further system’s development as well.